Dynamics and Challenges of Indonesian-ASEAN+3 Diplomatic Relationships in Handling Economic Recession and Mitigation the Covid-19 Outbreak in Indonesia - Hardi Alunaza; Anggi Putri; Annisa Ernianda; Fernandez Fernandez; Desy Nur Shafitri; Windy Widi Yanti; Muhammad Najeri Syahrin (Asean Study Center Lambung Mangkurat University, 2021)
The global pandemic crisis that has occurred since 2020 has affected Indonesia's economic growth. Not only is it going through a recession, but Indonesia is also considered slow to deal with Covid-19 domestically. This article attempts to describe how Indonesian diplomacy's dynamics and challenges with ASEAN+3 countries are coping with the economic recession and the mitigation of the Covid-19 pandemic in Indonesia. The data collection techniques that researchers use in this research are literature and documentation studies. Data analysis will also be performed when data is collected—this method raised by research books, writings, articles, and research reports. Besides, the authors also sought data relevant to this study of electronic media with reliable sources. Indonesia faced challenges with its existence in multilateral forums. It puts Indonesia in a tight position between achieving its national interests and fulfilling its international agenda obligations. While Indonesia was seen as the country with the worst handling of Covid-19, Indonesia aggressively pursues diplomacy and cooperation in handling and combating Covid-19. Indonesia's solution in dealing with and overcoming this pandemic's consequence is to partner with external parties, namely China, Japan, and South Korea in ASEAN+3 cooperations. Every country can work together in a condition of dependence and mutual need. In this case, ASEAN is working together to form ASEAN + 3 because it requires the three countries' experience in dealing with and overcoming the Covid-19 pandemic.